2020
DOI: 10.1101/2020.12.09.415901
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediction of Eye, Hair and Skin Color in Admixed Populations of Latin America

Abstract: We report an evaluation of prediction accuracy for eye, hair and skin pigmentation based on genomic and phenotypic data for over 6,500 admixed Latin Americans (the CANDELA dataset). We examined the impact on prediction accuracy of three main factors: (i) The methods of prediction, including classical statistical methods and machine learning approaches, (ii) The inclusion of non-genetic predictors, continental genetic ancestry and pigmentation SNPs in the prediction models, and (iii) Compared two sets of pigmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 53 publications
(134 reference statements)
1
2
0
Order By: Relevance
“…When analyzing eye color prediction made with the IrisPlex system, the prediction of intermediate colors in our population was inaccurate. In fact, none of the samples were predicted to be of intermediate color, showing concordance with other studies of mixed populations (Carratto et al., 2021; Marano et al., 2019; Palmal et al., 2021). It can be observed that in our predictions, intermediate colors show a considerable lack of definition when we use the markers included in the IrisPlex system, making this method more appropriate for a classification into two categories.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…When analyzing eye color prediction made with the IrisPlex system, the prediction of intermediate colors in our population was inaccurate. In fact, none of the samples were predicted to be of intermediate color, showing concordance with other studies of mixed populations (Carratto et al., 2021; Marano et al., 2019; Palmal et al., 2021). It can be observed that in our predictions, intermediate colors show a considerable lack of definition when we use the markers included in the IrisPlex system, making this method more appropriate for a classification into two categories.…”
Section: Discussionsupporting
confidence: 87%
“…We extracted DNA using Proteinase K (Promega, USA) and LiCl (Gemmell & Akiyama, 1996), and quantified it by using the Nanodrop spectrophotometer (Thermofisher). Then, we genotyped the samples for the six SNPs of the IrisPlex: rs12913832:A>G, rs1800407:C>T, rs12896399:G>T, rs16891982:C>G, rs1393350:G>A, and rs12203592:C>T, and additionally, another four SNPs: rs1129038:C>T, rs7183877:C>A, rs1800410:G>A and rs4778232:T>C. These polymorphisms are located in genes associated with eye color ( HERC2, OCA2, LOC105370627, SLC45A2, TYR , and IRF4 ) (Duffy et al., 2007; Eiberg et al., 2008; Eriksson et al., 2010; Frudakis et al., 2003; Han et al., 2008; Lippert et al., 2017; Liu et al., 2009; Palmal et al., 2021; Ruiz et al., 2013; Visser et al., 2012; Wollstein et al., 2017). We designed oligonucleotides with Primer‐BLAST (Ye et al., 2012) and performed polymerase chain reaction (PCR) using recombinant Taq polymerase (T‐Plus, Inbio‐Highway, Tandil, Argentina), as well as the thermocyclers MPI (La Plata, Argentina) and Biometra T3000 (Biosciences, Dublin, Ireland).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation